Effects of treated high-density polyethylene admixtures on the compressive strength of concrete in sulphates and acids environments - Iorwuese Anum; Frank Ndanusa Williams; Wyom Paul Zakka; Namala Amuga Keftin (Discover Civil Engineering)
Abstract Using plastic materials in cementitious matrices has spurred studies with the potential for sustainable concrete production. This study investigated the effect of high- density polyethylene (HDPE) on the compressive behavior of concrete in sulphates and acidic environments. The HDPE was pulverised and chemically treated with 20% hydrogen peroxide. The admixture was then added by the weight of cement in percentages (0, 0.25, 0.5, 0.75, and 1) to make concrete of 25 and 50 grades using 150mm3 steel moulds. Water-to-cement ratios of 0.4 and 0.36 were chosen. The cubes were initially cured in water for 28 days before being immersed in 10% tetraoxosulphate (vi) acid and 10% magnesium sulphate for 7, 28, and 90 days. The Strength Deterioration Factor (SDF) was then determined. The findings revealed that after 90 days of exposure, grade M25 cubes lost a maximum of 85.20% of their strength, while grade M50 cubes lost 76.69%. However, resistance to sulphate attack decreased with HDPE dose; grade M25 cubes showed the lowest strength loss of 5.7%, while grade M50 cubes showed the lowest strength loss of 4.67% both with 1% HDPE by weight of cement. The study concluded that pulverised and treated HDPE could improve concrete's resistance to sulphates. The study’s insights portend significant prospects for the production of sulphate-resistant cement while reducing the menace of plastic waste disposal. The study recommends the use of 1% pulverised HDPE by weight of cement for the production of concrete in sulphate resilient infrastructures.